Coastal Community Perceptions of the Purwa Shadow Puppet Performing Art - Pudjastawa, Astrid Wangsagirindra (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2022)
The purpose of this study was to determine the perception of coastal communities towards the art of wayang kulit purwa performances and examine the community's role in supporting the existence of the arts to survive and develop, using a qualitative method with a descriptive approach that uses observation and interview techniques with 25 residents of Masangan Village, Bungah, Gresik Regency and 2 puppeteers as resource persons. The results of this study indicate that (1) there are social and economic characteristics of the coastal community, (2) the perception of the coastal community towards an art performance and (3) the position of the wayang kulit purwa performing arts in the community. From the research results and discussion, it can be concluded that coastal communities consider the art of wayang kulit purwa performances to have an important position in their lives.